‘Even when you are afraid, you stay’: Provision of maternity care during the Ebola virus epidemic: A qualitative study - Jones, Susan; Sam, Betty; Bull, Florence; Pieh, Steven Bagie; Lambert, Jaki; Mgawadere, Florence; Gopalakrishnan, Somasundari; Ameh, Charles A.; van den Broek, Nynke (Midwifery, 2017)
to explore nurse-midwives understanding of their role in and ability to continue to provide routine and emergency maternity services during the time of the Ebola virus disease epidemic in Sierra Leone. a hermenuetic phenomenological approach was used to discover the lived experiences of nurse-midwives through 66 face to face interviews. Following verbatim transcription, an iterative approach to data analysis was adopted using framework analysis to discover the essence of the lived experience. health facilities designated to provide maternity care across all 14 districts of Sierra Leone. nurses, midwives, medical staff and managers providing maternal and newborn care during the Ebola epidemic in facilities designated to provide basic or emergency obstetric care. the healthcare system in Sierra Leone was ill prepared to cope with the epidemic. Fear of Ebola and mistrust kept women from accessing care at a health facility. Healthcare providers continued to provide maternity care because of professional duty, responsibility to the community and religious beliefs. nurse-midwives faced increased risks of catching Ebola compared to other health workers but continued to provide essential maternity care. future preparedness plans must take into account the impact that epidemics have on the ability of the health system to continue to provide vital routine and emergency maternal and newborn health care. Healthcare providers need to have a stronger voice in health system rebuilding and planning and management to ensure that health service can continue to provide vital maternal and newborn care during epidemics. •Nurse-midwives knew that they were at increased risk of contracting Ebola Virus infection but continued to provide essential maternity care.•Fear of contracting Ebola and mistrust kept women from accessing maternity care at a health facility.•Nurse-midwives remained in their posts because of a sense of professional duty, responsibility to the community and religious beliefs.•Nurse-midwives have an important role in health system planning and management ensuring the health system is rebuilt, to provide vital care including during future epidemics.